PENGUASAAN TAJWID DENGAN METODE AN-NAHDLIYAH DALAM PEMBELAJARAN YANBU'A KELAS 4 TPQ RAUDHLOTHUT THULLAB KEMIRI MOJOTENGAH WONOSOBO - Ria Tri Hartini; Nur Lu’lu’ul Maknunah; Rindiana Rindiana; Denisa Amni Nabilah Amin; Muhammad Khairy Abdullah Dzaky; Fatkhurrohman Fatkhurrohman (CV. KAMPUS AKADEMIK PUBLISING, 2026)
This study aims to describe the implementation of the An-Nahdliyah method in Yanbu’a learning, identify the supporting and inhibiting factors affecting tajwid mastery, and analyze the effectiveness of the An-Nahdliyah method in improving the tajwid mastery of fourth-grade students at TPQ Raudhlothut Thullab Kemiri Mojotengah Wonosobo. This research employed a descriptive qualitative approach, with data collected through observation, interviews, and documentation. The results of the study indicate that: 1) the implementation of the An-Nahdliyah method in fourth-grade Yanbu’a learning is carried out in a structured and consistent manner through classical learning, emphasizing rhythmic beats (ketukan), imitation (taqlid), and repetition. The learning process begins with the teacher providing correct recitation examples in accordance with tajwid rules, followed by collective rhythmic recitation, individual reading practice, and direct correction of errors related to letter articulation (makhraj), letter characteristics, and recitation rules. This method functions as a habituation process to accustom students to reciting the Qur’an in a tartil manner and in accordance with tajwid principles. 2) the supporting factors for tajwid mastery include the competence of teachers in applying the An-Nahdliyah rhythmic technique, students’ enthusiasm and motivation, a conducive learning environment, and a regular learning schedule. Meanwhile, the inhibiting factors include differences in students’ initial abilities, limited instructional time, less optimal individual guidance, and a lack of recitation practice at home. 3) the effectiveness of the An-Nahdliyah method in improving tajwid mastery is categorized as good, as indicated by increased accuracy in letter articulation, application of letter characteristics, and tajwid rules such as mad, nun sakinah, and mim sakinah. Nevertheless, the improvement in tajwid mastery has not been evenly achieved among all students, indicating the need for reinforcement through individual guidance as a complement to classical learning in order to achieve more optimal results.